INFLUENCE OF MILK AND SOME SUDANESE MEALS ON THE DISSOLUTION OF CIPROFLOXACIN TABLETS - M.M., Maatoug; A.F, Mustafa; M.A., Yousif (Gezira Journal of Health Sciences, 2010)
For a drug to be effective , it must be released from the dosage form , fully dissolved in the gastro-intestinal fluids ,  be stable as solution in the gastro-intestinal fluids,  pass through the gastrointestinal barriers into the mesenteric circulation  without being  metabolized , pass through the liver into the systemic circulation unchanged and reach its site of action. Food  is one of the factors which interfere with these processes. The effect of Sudanese meals will  be different due to their high contents of fats, proteins and fibers    This study  aimed to  determine the influence of milk and some Sudanese meals (Foul – Vicia faba - , “Gorrassah with damaa” and “ Kissraa with sharmoot” )on the dissolution of ciprofloxacin HCl  tablets and hence bioavailability. The influence of milk and the mentioned Sudanese meals on the dissolution of ciprofloxacin was studied using paddle dissolution apparatus. The dissolution of the drug was measured in the presence of each meal individually using U.V-  visible spectrophotometer. The samples were taken with 5 minutes intervals  up to 30minutes The results obtained were compared to the results of the dissolution of this drug in simulated gastric fluid in fast state [0.1 N HCl]. The study revealed that the dissolution of ciprofloxacin in Sudanese meals is lower than its dissolution in milk- whose reduction of dissolution of ciprofloxacin was mentioned in a lot of studies world-wide. The order of the influence of Sudanese meals, used in the study,  was foul followed by kissraa then  gorrasah which showed that the influence was directly proportional to the viscosity of the meal.  Using two different volumes of foul ,the study revealed that influence of meals on the dissolution of ciprofloxacin was significant even small amounts were used.